2011
DOI: 10.3892/mmr.2011.722
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib suppresses fibroblast proliferation and collagen expression by inhibiting ERK1/2 and SMAD2/3 phosphorylation

Abstract: Abstract. This study aimed to investigate whether celecoxib suppresses fibroblast proliferation and collagen expression by inhibiting extracellular signal-regulated kinase 1/2 (ERK1/2) and SMAD2/3 phosphorylation. Celecoxib was added to NIH/3T3 fibroblasts stimulated by fibroblast growth factor-2 (FGF-2) or transforming growth factor-β1 (TGF-β1). NIH/3T3 fibroblast proliferation and viability were assessed by MTT assays; ERK1/2 expression and SMAD2/3 expression were assessed by quantitative RT-PCR and Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It is known that Cox-2 inhibition can affect the proliferative state of fibroblasts in vitro [33]. Therefore, we hypothesized that ASA treatment could influence numbers of tumor-infiltrating CAFs in principle.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that Cox-2 inhibition can affect the proliferative state of fibroblasts in vitro [33]. Therefore, we hypothesized that ASA treatment could influence numbers of tumor-infiltrating CAFs in principle.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β1 induced phosphorylation of Smad3 and increased Col3 expression, which can be prevented by Smad3 depletion (30). Previous studies have strongly indicated that Erk1/2 plays a synergistic role in Smad-mediated collagen synthesis, as initiated by TGF-β1 in some cells of fibrotic diseases such as human dermal fibroblasts and myofibroblasts (31, 32). However, it is not well known what roles Erk1/2 play in activating Smad3.…”
Section: Discussionmentioning
confidence: 99%